Encapsulated Papillary Thyroid Tumor with Delicate Nuclear Changes and a Mutation as a Possible Novel Subtype of Borderline Tumor - Kenji Ohba; Norisato Mitsutake; Michiko Matsuse; Tatiana Rogounovitch; Nobuhiko Nishino; Yutaka Oki; Yoshie Goto; Kennichi Kakudo (Korean Society of Pathologists & the Korean Society for Cytopathology, 2019)
Although papillary thyroid carcinoma (PTC)-type nuclear changes are the most reliable morphological feature in the diagnosis of PTC, the nuclear assessment used to identify these changes is highly subjective. Here, we report a noninvasive encapsulated thyroid tumor with a papillary growth pattern measuring 23 mm at its largest diameter with a nuclear score of 2 in a 26-year-old man. After undergoing left lobectomy, the patient was diagnosed with an encapsulated PTC. However, a second opinion consultation suggested an alternative diagnosis of follicular adenoma with papillary hyperplasia. When providing a third opinion, we identified a low MIB-1 labeling index and a heterozygous point mutation in the KRAS gene but not the BRAF gene. We speculated that this case is an example of a novel borderline tumor with a papillary structure. Introduction of the new terminology "noninvasive encapsulated papillary RAS-like thyroid tumor (NEPRAS)" without the word "cancer" might relieve the psychological burden of patients in a way similar to the phrase "noninvasive follicular thyroid neoplasm with papillary-like nuclear features (NIFTP)."